Factors in Controlling the Successful Peer Teaching Method in Higher Education - Komm Pechinthorn; Jirangrug Samarkjarn; Nico Irawan (ELLITE, 2020)
This educational research paper was conducted by using questionnaires to collect the essential student survey data. The source of the study was a chosen mid-sized English for Everyday Use subject of 60 students in a public university under the International College of Rajamangala University Krungthep (ICUTK) in the capital city, Bangkok district in Thailand with the time frame from June to October 2019.The research employed multiple regression equation models by Minitab version 18 to study the structural relationships on satisfactions of peer teaching methodology, meaning that students were required to teach their peers instead of teachers in classroom. The selected variables were gender, GPA, age and attendance of the students. A major contribution of this education research was its significant direct relationship which mediated the method of teacher and student learning by testing the peer teaching methodology in classroom compared to the traditional classroom. Clear descriptive statistics such as mean, standard deviations were provided from the calculation and multiple regressions analysis shows the coefficients, t-stats, errors and significant values of each selected variables. Moreover, the calculation model for those variables was formed for the future prediction for the related educators. The results indicated the importance of peer teaching method in class room for student learning supporting by the highly satisfied scores have impact on all variables included in this research.